GE_GERICHTE C/2490/2017 vom 11. Januar 2019 - GE Cour de justice (2019)
SALAIRE ; PRÊT À USAGE ; COMPENSATIO ; SUBROGATION ; ULTRA PETITA ; MONNAIE(UNITÉ MONÉTAIRE) | CPC.58.al1; CO.323.al4; CO.312; CO.120.al1; CO.84.al1; CMVMS.337.al3.letc